ChemInform Abstract: Robust, Chiral, and Porous BINAP‐Based Metal—Organic Frameworks for Highly Enantioselective Cyclization Reactions. Issue 10 (February 2016) - Sawano, Takahiro; Thacker, Nathan C.; Lin, Zekai; McIsaac, Alexandra R.; Lin, Wenbin
Abstract: BINAP‐based metal‐organic frameworks and their postsynthetic metalation with Rh‐complexes are designed and used as highly active and enantioselective single‐site solid catalysts for the enantioselective reductive cyclization and Alder‐ene cycloisomerization of 1, 6‐enynes as well as for Pauson—Khand cyclization reactions between 1, 6‐enynes and cinnamaldehyde as the CO source.